Spatio-Temporal Level Variations of the Martian Seasonal North Polar Cap From Co-Registration of MOLA Profiles - Xiao, Haifeng; Stark, Alexander; Schmidt, Frédéric; Hao, Jingyan; Steinbrügge, Gregor; Wagner, Nicholas L.; Su, Shu; Cheng, Yuan; Oberst, Jürgen (Journal of Geophysical Research: Planets, 2022)
International audience The seasonal deposition and sublimation of CO 2 constitute a major element in Martian volatile cycles. We reprocess the Mars Orbiter Laser Altimeter (MOLA) data and apply co-registration procedures to obtain spatio-temporal variations in levels of the Seasonal North Polar Cap (SNPC). The maximum level over the Residual North Polar Cap (RNPC) is 1.3 m, approximately half of that at the south pole (2.5 m). However, the maximum level in the dune fields at Olympia Undae can be up to 3.8 m. Furthermore, off-season decreases up to 3 m during the northern winter at Olympia Undae are observed. These are likely due to metamorphism effects accentuated by the reduced snowfall at this period. Meanwhile, off-season increases of up to 2 m during the northern spring are noted, the cause of which remains to be explored. The volume of the SNPC peaks at the end of northern winter and is estimated to be approximately 9.6 × 10 12 m 3 , which is 2% more than that of the Seasonal South Polar Cap. The bulk density of the SNPC can go through phased decreases in accordance with phased accumulation at northern high-latitudes. These findings can put important constraints on the Martian volatile cycling models.